2015
DOI: 10.1186/s12879-015-0791-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling undetected live poliovirus circulation after apparent interruption of transmission: implications for surveillance and vaccination

Abstract: BackgroundMost poliovirus infections occur with no symptoms and this leads to the possibility of silent circulation, which complicates the confirmation of global goals to permanently end poliovirus transmission. Previous simple models based on hypothetical populations assumed perfect detection of symptomatic cases and suggested the need to observe no paralytic cases from wild polioviruses (WPVs) for approximately 3-4 years to achieve 95% confidence about eradication, but the complexities in real populations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 38 publications
4
84
0
Order By: Relevance
“…Prior mathematical modeling studies explored the probability of undetected circulation of WPVs in the absence of reported cases or poliovirus detections by an ES system. Our 2015 study (Kalkowska et al., ) used a stochastic adaptation of a poliovirus dynamic transmission model (Duintjer Tebbens et al., ) and included an analysis of the 2013 serotype 1 WPV introduction into Israel followed by more than a year of transmission detected by the extensive ES system in Israel (Kalkowska et al., ). The study considered the impact of acute flaccid paralysis (AFP) surveillance and ES on the confidence about no undetected poliovirus circulation as a function of time after the last detection through either system (Kalkowska et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior mathematical modeling studies explored the probability of undetected circulation of WPVs in the absence of reported cases or poliovirus detections by an ES system. Our 2015 study (Kalkowska et al., ) used a stochastic adaptation of a poliovirus dynamic transmission model (Duintjer Tebbens et al., ) and included an analysis of the 2013 serotype 1 WPV introduction into Israel followed by more than a year of transmission detected by the extensive ES system in Israel (Kalkowska et al., ). The study considered the impact of acute flaccid paralysis (AFP) surveillance and ES on the confidence about no undetected poliovirus circulation as a function of time after the last detection through either system (Kalkowska et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Our 2015 study (Kalkowska et al., ) used a stochastic adaptation of a poliovirus dynamic transmission model (Duintjer Tebbens et al., ) and included an analysis of the 2013 serotype 1 WPV introduction into Israel followed by more than a year of transmission detected by the extensive ES system in Israel (Kalkowska et al., ). The study considered the impact of acute flaccid paralysis (AFP) surveillance and ES on the confidence about no undetected poliovirus circulation as a function of time after the last detection through either system (Kalkowska et al., ). The results suggested that it takes up to three years without paralytic cases to reach 95% confidence about no circulation in the context of perfect (i.e., detecting every case) AFP surveillance (without ES).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations